Organic matter sources in permafrost peatlands changed by high-intensity fire during the last 150 years in the northern Great Khingan Mountains, China - Cong, Jinxin; Wang, Guoping; Han, Dongxue; Gao, Chuanyu (Palaeogeography, palaeoclimatology, palaeoecology, 2023)
Peatlands store nearly 30% of global soil carbon, and they are widely distributed in mid- to high latitude regions that are sensitive to climate change and recently subject to more frequent fires. Fire not only causes direct effects on the growth of plant communities but also results in significant effects on organic matter (OM) sources and the stability of peatland carbon reservoirs; however, these long-term impacts are poorly understood, especially for permafrost peatlands. Based on a 210Pb age-depth model, we reconstructed historical variations in OM sources using the chemical properties of peatland sedimentary records at a site in the northern Great Khingan Mountains of China. Compared with the historical fire intensity and fuel sources reconstructed by the FTIR spectrum of pyrogenic carbon (PyC), the effects of fire on OM sources were analyzed for the last 150 years. Our results show that historically >70% of OM in the studied peatlands was sourced from shrubs, especially before 1980. Due to high-intensity fires which more easily burn herb plant litter, the major OM sources in burnt sites were shrubs, and herb plant litters were the major PyC sources. With fire management policies implemented at the end of the 1970s, fire frequency and intensity decreased markedly leading to a gradual decrease in the proportion of shrub OM from 75% to 50% from 1980 to 2000. Although fire intensity has increased since 2000, fire management interventions quickly extinguish most fires and decrease the effects of fires on herb plant litters. Both climate warming and high-intensity fire promote more herbs growing in burned peatlands, and the residual herb/moss plant litters became the major OM sources after 2000. •Impact of fire on long-term peatland organic matter (OM) sources was evaluated.•High intensity fires led the major sources of residual OM in peatlands being shrubs.•Herb plant litters more easily consumed and converted to pyrogenic carbon.•Fire management policies decrease the shrub OM proportion from 75% to 50% after 1980.•Climate warming and fire control led the herb/moss being the major OM sources.